2019
DOI: 10.1590/1678-4499.20180178
|View full text |Cite
|
Sign up to set email alerts
|

Timing and growing conditions of nitrogen topdressing influence the grain yield and protein content of four wheat cultivars

Abstract: Tukey's test (p ≤ 0.01) were used. The interaction between cultivars and environments influence all yield components, GY and PC. The interaction management forms of N and environments affected the TKW, NEA, GY and PC. The results showed that in low-rainfall environments, nitrogen topdressing could be suppressed with no negative effects on GY or PC. Under ideal weather conditions, the GY of wheat cultivars was enhanced on application of 60 kg.ha-1 N of urea at the beginning of tillering as well 20 kg.ha-1 of N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The grain protein formation requires suitable soil N availability for plant uptake, even during the grain-filling stage, because the N accumulated in the plant biomass is preferentially remobilized for the starch formation and, posteriorly, rises the grain protein concentration (Silva et al, 2019). In this context, Mosanaei et al (2017) and Ma et al (2019), studying the effects of N fertilization on wheat crops, verified that increasing N rates increased the grain protein concentration.…”
Section: Technological Quality Of Grains and Flour As Influenced By N...mentioning
confidence: 80%
See 1 more Smart Citation
“…The grain protein formation requires suitable soil N availability for plant uptake, even during the grain-filling stage, because the N accumulated in the plant biomass is preferentially remobilized for the starch formation and, posteriorly, rises the grain protein concentration (Silva et al, 2019). In this context, Mosanaei et al (2017) and Ma et al (2019), studying the effects of N fertilization on wheat crops, verified that increasing N rates increased the grain protein concentration.…”
Section: Technological Quality Of Grains and Flour As Influenced By N...mentioning
confidence: 80%
“…The concentrations of protein and gluten in the grains are determined by genetics and influenced by environmental conditions, such as temperature and availability of nutrients and water (Guarienti et al, 2004;Rozbicki et al, 2015;Savill et al, 2018). For instance, during the grain-filling stage, the N accumulated in the plant biomass is preferentially remobilized to produce starch and, posteriorly, to increase the grain protein concentration (Silva et al, 2019;Lollato et al, 2021), which depends on the water supply throughout this period. Thus, in the condition of drought stress, the protein/starch ratio changes in the direction of protein, resulting in smaller wheat grains with a higher protein concentration (Blumenthal et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Paymann [54] reported that protein content did not significantly differed due to split schedules of nitrogen application. Silva et al [55] also reported that wheat cultivars and nitrogen scheduling did not impose its significant effect on protein content. N6 (9.28%) and N5 (9.18%).…”
Section: Yield Of Maizementioning
confidence: 96%
“…Nitrogen is a major responsible factor in achieving optimum grain yield and quality [ 15 ] and surprisingly, compared to other fertilizer types it needs special management practices [ 16 ]. Depending on the type of fertilizer used, nitrogen is characterized by rapid uptake by plants, highly mobile in the soil (subject to leaching and volatilize as NH 3 ), denitrification, immobilization by microbes, forming complex with soil organic matter (humus) and fixed in 2:1 clay minerals [ 17 , 18 ]. Thus, Ghafoor et al [ 19 ] reported that nitrogen is the most frequently deficient nutrient than others.…”
Section: Introductionmentioning
confidence: 99%